The Effects of Sustained Literacy Engagement on Cognition and Sentence Processing Among Older Adults - Stine-Morrow, Elizabeth A. L.; McCall, Giavanna S.; Manavbasi, Ilber; Ng, Shukhan; Llano, Daniel A.; Barbey, Aron K. (Frontiers in Psychology, 2022)
Considerable evidence suggests that language processing depends on memory processes, which are vulnerable to declines with aging. Yet little is known about the effects of sustained literacy engagement on memory and other aspects of cognition. In the current study, adults (60 to 79 years of age) were randomly assigned to an eight-week program of leisure reading (n=38) or to an active puzzle control (n=38). Relative to the control, the experimental group showed differential improvement in verbal working memory and episodic memory. The experimental group also showed evidence of enhanced conceptual integration in sentence processing. These effects did not vary as a function of personality characteristics (e.g., openness) hypothesized to be compatible with literacy engagement. These findings support the idea that the exercise of cognitive capacities in the context of everyday life may offset age-related impairment in areas of cognition engaged by the activity, regardless of dispositional fit.